MULTI-SCALE ANALYSIS OF CRYOGENIC COMPOSITE STRUCTURES CONSIDERING INTERFACIAL PHASE - ZHANG XiaoWen; XING HanZheng; ZHANG JingKun; REN MingFa (Jixie qiangdu)
Fiber/matrix interfaces exist in the transitional region between fiber and resin matrix in fiber reinforced composites. How to reasonably consider the interposition of interfacial phase is a critical problem in the failure analysis of composite structures. In this paper, a multi-scale finite element method is proposed based on three-phase representative volume element, by developing the microscopic failure criterion, damage degradation model and uncertainty model of material strength. The failure prediction of low temperature composite structure under thermal mechanical load is realized by the multi-scale finite element method. Moreover, the method is used to analyze the failure of composite laminates at five temperatures. The numerical predictions are in good agreement with the experimental results, which shows that the method can analyze the failure of composite structures at cryogenic temperatures effectively.